Self and narrative in schizophrenia: time to author a new story. Issue 2 (5th December 2005) - Roe, D; Davidson, L
Abstract : The prevailing, clinical view of schizophrenia, as reflected in the psychiatric literature, suggests both that people with schizophrenia have lost their sense of self and that they have a diminished capacity to create coherent narratives about their own lives. Drawing on our empirical research in the growing area of recovery, we describe not only the disruptions and discontinuities introduced by the illness and its social and personal consequences, but also the person's efforts to overcome these, to reconstruct a sense of self, to regain agency and to create a coherent life narrative. We suggest in closing that, rather than simply being a byproduct of recovery, these processes of re-authoring one's life story are actually integral components of the recovery process itself.